Glutathione and neurodegenerative diseases: immunopharmacological implications - Knudsen, Ethan; Tadje, Jaxson; Coggins, Carter; Venketaraman, Vishwanath (Frontiers in Pharmacology, 2026)
Neurodegenerative diseases are characterized by progressive neuronal dysfunction, often accompanied by chronic inflammatory states and redox imbalance within the central nervous system (CNS). Glutathione (GSH), a key regulator of oxidative stress and cellular immunity, has a critical role in modulating the functional states of CNS-resident and infiltrating immune cell subsets. This review aims to synthesize emerging evidence on how GSH depletion contributes to impaired immune and antioxidant activity in neurodegenerative diseases, such as Parkinson’s Disease (PD), Alzheimer’s Disease (AD), and multiple sclerosis (MS). By exploring how redox signaling via GSH influences inflammatory immune phenotypes across different disease states, we will isolate possible therapeutic interventions for treatment of these conditions. By characterizing GSH’s function and designating it as a special regulator of immune cell behavior, this review highlights its potential as both a therapeutic agent and biomarker for patients with neurodegenerative conditions.